2009
DOI: 10.1197/jamia.m3091
|View full text |Cite
|
Sign up to set email alerts
|

Natural Language Processing Framework to Assess Clinical Conditions

Abstract: OBJECTIVE The authors developed a natural language processing (NLP) framework that could be used to extract clinical findings and diagnoses from dictated physician documentation. DESIGN De-identified documentation was made available by i2b2 Bio-informatics research group as a part of their NLP challenge focusing on obesity and its co-morbidities. The authors describe their approach, which used a combination of concept detection, context validation, and the application of a variety of rules to conclude patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…They reported 97 % accuracy in predictions of disease status, which was comparable to that of humans. Ware and colleagues [ 325 ] also used the i2b2 NLP programs to focus on extracting diagnoses of obesity and 16 related diagnoses from textual dis-charge summary reports. They reported better than 90 % agreement with clinical experts as the comparative "gold standard."…”
Section: Querying Medical Textmentioning
confidence: 99%
“…They reported 97 % accuracy in predictions of disease status, which was comparable to that of humans. Ware and colleagues [ 325 ] also used the i2b2 NLP programs to focus on extracting diagnoses of obesity and 16 related diagnoses from textual dis-charge summary reports. They reported better than 90 % agreement with clinical experts as the comparative "gold standard."…”
Section: Querying Medical Textmentioning
confidence: 99%
“…The 2007 challenge [2] aimed at identification of obesity status of patients and associated co-morbidities using discharge summaries. Ware et al [10] developed a system where a principal concept of interest was identified using regular expressions and then surrounding context was searched for secondary concepts. Final decisions were made using these two sets of concepts.…”
Section: Related Workmentioning
confidence: 99%
“…Natural language processing tools show considerable promise in converting free text into structured data,43 but these tools are far from perfected 44. In a recent unpublished analysis of free text for patient encounters for otitis media on a single day , a research group at the Children’s Hospital of Philadelphia encountered 278 different ways in 465 EMR notes to express the fact that patients had temperature > 102.0 F (e.g.…”
Section: Electronic Medical Records and Clinical Researchmentioning
confidence: 99%